What Should We Understand From the Term “islamic Philosophy” - Gafarov, Anar (Scholarya Demo Journal of Ruby, 2019)
The terms form a map of our mind. We describe and express the events weencounter, the processes we imagine, and our feelings and thoughts that weexpress them by the literary-philosophical expressions by means of terms. It ispossible peculiarly by means of terms to assert the theories by abstraction aboutthe existence and events, and to think about the determination of legalities andunderstanding and sense-making of them. Having a broad imagination related tothe terms is also of great importance in terms of formulating new terms anddefinitions in our mind world. The terms are the key of thought. It shoud be notedthat the terminological poverty of mind is less dangerous than faulty perceptionof terms. The format attempt of concepts in our mind by terms with essentiallyfaulty and meaning loss is like journey with the wrong map. Therefore, first of all,it is necessary to achieve accurate information and imagery related to the terms.Taking this point into the consideration we will discuss in this article one of theterms, “Islamic philosophy” that is necessary to formulate the right idea about it.Furthermore, the study of the term “Islamic philosophy” is important in termsof our next works, “The problem of the Source of Morality in Philosophy in Termsof Metaphysic and Epistemology” that we are going to study the source ofmorality in terms of Islamic Philosophy there too. So, this matter naturally drivesus to clarify firstly the term of Islamic Philosophy in our dissertation.Otherwise, the second reason of the study about the term Islamic Philosophyis that there is faulty and untruthful knowledge about Islamic philosophy in thephilosophical studies and works in Azerbaijan. In the sense, the main goal in thearticle is to formulate a correct idea related to the term “Islamic philosophy”. The main thesis of the article is that the term "Islamic philosophy" refers tothe philosophy of the philosophers that dealing with philosophical creativity inIslamic cultural geography irrespective of their religious or ethnic identity.